Analisis Novel Mawar, Bukan Nama Sebenarnya Karya Dian Purnomo: Kajian Feminisme Radikal - Putri Ratih Septariyani; Syfani Zara Ranzani; Dyah Hesti Retnaningtyas; Sutri Sutri (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the forms of women’s oppression and patriarchal power relations based on Kate Millett’s radical feminist perspective. The study employed a qualitative descriptive method with a feminist literary criticism approach. The data source was a novel by Dian Purnomo analyzed through reading and note-taking techniques. The findings revealed that female characters experienced various forms of gender injustice, including ideological, biological, sociological, coercive, myth and religion, and psychological aspects. Patriarchy in the novel is represented through control over women’s bodies, sexual violence, subordination, victim blaming, and psychological pressure that place women in subordinate positions. This study shows that literary works can represent social realities related to patriarchal domination and function as a medium of criticism toward gender inequality in society.